Formal strategic planning, operating environment, size, sector and performance: Evidence from the UK’s manufacturing SMEs - Thomas, Howard (Institutional Knowledge at Singapore Management University, 2009)
The relationship between strategic planning and firm performance has long interested strategic management researchers. In the past decade, this research effort has slowed down, while strategic planning has gained greater popularity among managers. However, some academics dispute the usefulness of strategic planning, particularly in turbulent environments. This paper examines the following key research questions that are relevant to both practice and theory. First, the relationship between the formality of strategic planning (conceptualised by considering whether firms have written strategic plans and the level of correspondence between the written strategic plan and the normative planning process) and a wide range of performance measures. Second, the relationship between three contingency factors - size, sector and environment, in addition to the incidence of formal planning and the level of formality. Of great interest are the effects of munificence and turbulence. The results suggest that the link between strategic planning formality and performance is tenuous. Nevertheless, managers tend to deploy strategic planning widely in difficult market environments. The conclusion is that strategic planning is perceived to enhance a firm's survival chances, but not necessarily its short-term performance.